ОБ ОДНОКОРНЕВОЙ АНТОНИМИИ ИМЕН СУЩЕСТВИТЕЛЬНЫХ В РУССКОМ И ПОЛЬСКОМ ЯЗЫКАХ - Nowak, Katarzyna (Studia Rossica Posnaniensia, 2008)
Different kinds of substantival same-root antonyms in Russian and Polish have been presented in the article. Special attention has been paid to the specific variety of same root antonymy, i.e. derivational antonymy.